Strengthening The Attitude of Religious Moderation Through the Study of Tolerance Values in Al-Munir’s Tafsir - Akif Khilmiyah; Ahmat Wahyudi (Didaktika Religia, 2021)
With the emergence of various conflicts due to differences in religious views, it is necessary to prevent and increase awareness of the importance of religious moderation in society through studying the values of tolerance in Al Munir's Tafsir. This study aims to examine the content of tolerance values in QS. al-Kāfirūn in Tafsir al-Munῑr to strengthen the attitude of religious moderation. This type of research was library research with a qualitative approach. The primary source was from the book Tafsir al-Munῑr by Wahbah Az-Zuḥaili, and the secondary sources were relevant to this research. The documentation collected data. Then the data were analyzed using descriptive analysis and content analysis. The results showed that al Munir's Tafsir of Tolerance values on QS. Al-Kāfirūn covers aspects of aqidah, shari'ah and morals. The Akidah aspect contains respect for non-Muslim beliefs, but not to the point of justifying them because a Muslim must believe that the only true religion is Islam. The Sharia aspect contains worship and muamalah. The Worship aspect has given the freedom to non-Muslims to worship according to their beliefs. The Muamalah aspect includes orders to be fair to non-Muslims. The moral element contains the command to speak softly but also applies harshly and firmly when non-Muslims disturb the creed of Muslims. The implication of this research for the community is that a correct understanding of tolerance will increase the attitude of religious moderation in society so that religious harmony can be realized.